Policies of the Regional Government of Bangkalan Regency in Improving the Development of the Fisheries Sector in the Coastal Region - Rosalina Mega Putri; Ika Devy Pramudiana; Aris Suryana; Sri Kamariyah (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study aims to describe and analyze the policies of the Bangkalan Regency Regional Government in increasing development in the fisheries sector in coastal areas, as well as the supporting and inhibiting factors for development in the sector. Data collection techniques include interviews, observations, and documentation. Research informants are from the Bangkalan Regency Bappeda, the Bangkalan Regency Agriculture Office, the Bangkalan Regency Government in the field of development, and district and village offices. The data analysis technique uses the interactive model developed by Miles et al. (2014), namely data condensation, data presentation, and conclusion drawing. The results of the study show that the policies of the Bangkalan Regency Regional Government in increasing development in the fisheries sector in coastal areas have accommodated the interests of the community, especially in the fisheries sector, which touches all levels of society, so the development policies implemented run as planned. The process of communicating and delivering information about fisheries development policies, especially in coastal areas, is carried out through meetings between Muspika and the Fisheries Service, attended by all appointed employees to participate in socializing fisheries development policies. The efforts made by the Bangkalan Regency Regional Government in increasing development in the fisheries sector in coastal areas include utilizing fisheries experts to be involved in program implementation. The commitment of the Bangkalan Regency Regional Government in improving development in the fisheries sector in coastal areas is demonstrated by carrying out the agency's vision and mission, namely realizing the fisheries sector in Bangkalan Regency as a center for integrated fisheries economic growth and development with sustainable resource and fisheries management. The Bangkalan Regency Regional Government coordinates and cooperates with related parties in the implementation of the fisheries sector development policy. Supporting factors include institutional support in the form of donations and ideas from the community in planning, as well as support from the private sector and NGOs in community economic empowerment. Inhibiting factors include inadequate institutional facilities and infrastructure, the wide and separated target areas, and the community's mindset, which is still not responsive to development programs.